Prevalence and relationship between burnout and depression in our future doctors: a cross-sectional study in a cohort of preclinical and clinical medical students in Ireland. Issue 4 (1st May 2019) - Fitzpatrick, Orla; Biesma, Regien; Conroy, Ronán M; McGarvey, Alice
Abstract : Objectives: This cross-sectional study was designed to measure burnout and its impact on risk of depression in a medical student population, comparing the preclinical and clinical years. Design: We conducted a survey of 269 medical school students in both preclinical and clinical years at the Royal College of Surgeons in Ireland, using the Beck Depression Inventory-Fast Screen (BDI-FS), the Maslach Burnout Inventory-Student Survey and items assessing willingness to use mental health services. Burnout scores were calibrated to probability of depression caseness and classified as low risk (<25%), intermediate (25%–50%) and high risk (>50%) of depression. Results: There was a 39% (95% CI 33% to 45%) prevalence of depressive caseness based on a score of ≥6 on the BDI-FS. Prevalence did not vary significantly between clinical and preclinical years. The rate of burnout varied significantly between years (p=0.032), with 35% in the high-burnout category in clinical years compared with 26% in preclinical years. Those in the low burnout category had a 13% overall prevalence of depressive symptoms, those in the intermediate category had a 38% prevalence and those in the high category had a 66% prevalence of depressive symptoms. Increasing emotional exhaustion (OR for one—tertile increase in score 2.0, p=0.011) and decreasing academic efficacy (OR 2.1, p=0.007) increased the odds of being unwilling to seek help for mental health problems (11%). Conclusion: While previous studies have reported significant levels of burnout and depression, our method of calibrating burnout against depression allows burnout scores to be interpreted in terms of their impact on mental health. The high prevalences, in line with previous research, point to an urgent need to rethink the psychological pressures of health professions education.